Pemetaan Sosial Masyarakat di Pulau Semujur Kabupaten Bangka Tengah - Wahri Sunanda; Luna Febriani; Herman Aldila (Universitas Pamulang, 2023)
Semujur Island is one of the islands in the administrative area of Central Bangka Regency, to be precise in Kebintik Village, Pangkalan Baru District. Dominantly the existing land of Semujur Island is in the form of gardens/fields and shrubs with trees that are rarely found in the east. The residential area has supporting facilities in the form of roads and docks which are concentrated on the west side of Semujur Island. The majority of residents who inhabit Semujur island come from immigrant communities (Buton, Tanjung Gunung, and Sungai Selan) which are dynamic with their main occupation as fishermen. The high level of community harmonization makes the potential for community social conflict on this island quite low. The condition of the island is still natural and the social environment where conflicts rarely occur as well as the construction of infrastructure facilities such as docks, mosques, and tourist shelters by the local government make this island suitable for use as a place for permanent residence and the development of a new tourism sector with potential. In addition, based on the measurement results of environmental parameters, it is concluded that the current quality of the waters around Semujur Island is still relatively good even though the pH level of the waters as a whole is alkaline. This allows it to be used for microalgae cultivation which is expected to open up new business opportunities so that it can improve the economic conditions of the residents and suppress the demographic dynamics of the Semujur Island community.